PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP PENALARAN MATEMATIS PESERTA DIDIK KELAS VIII SMPN 8 PADANG - Dia Hayati (Departemen Matematika, 2019)
Mathematical reasoning ability is one of the eight goals of mathematics learning that must be achieved. However, in the fact the mathematical reasoning abilities of Grade VII students in Padang 8 Junior High School were still low. One effort to improve student’s mathematical reasoning ability was to apply the cooperative learning model type Group Investigation. The purpose of this study was to compare the mathematical reasoning abilities of students who learn using the cooperative learning model type Group Investigation with conventional learning in class VII of SMP 8 Padang. This type of research was a quasi-experimental study with the design of Static Group Design. Based on the results of the research conducted, it can be concluded several things as follows. obtained P-value = 0.028 < α = 0.05, so in other words mathematical reasoning ability that is learning using the cooperative learning type Group Investigation model is better than those who learn using conventional learningKeywords – cooperative learning model, Group Investigation, Mathematical reasoning ability.